Highly Thermal Stable TATB‐based Aluminized Explosives Realizing Optimized Balance between Thermal Stability and Detonation Performance. Issue 12 (26th October 2017) - Gong, Feiyan; Guo, Hu; Zhang, Jianhu; Shen, Chunying; Lin, Congmei; Zeng, Chengcheng; Liu, Shijun
Abstract: In this work, a series of TATB‐based aluminized explosives were formulated from 1, 3, 5‐triamino‐2, 4, 6‐trinitrobenzene (TATB), aluminum powders and polymeric binders. The thermal stability, heat of detonation, detonation velocity and pressure of the TATB based aluminized (TATB/Al) explosives were systematically investigated by cook‐off, constant temperature calorimeter, electrometric method and manganin piezo resistance gauge, respectively. The selected PBX‐3 (70 wt% TATB/25 wt% Al/5 wt% fluorine resin) achieved optimized balance between thermal stability and detonation performance, with the thermal runaway temperature around 583 K. The thermal ignition of TATB‐based aluminized explosive occurred at the edge of the cylinder according to the experimental and numerical simulations. Moreover, the critical thermal runaway temperature for PBX‐3 was calculated based on the Semenov's thermal explosion theory and the thermal decomposition kinetic parameters of the explosive, which was consistent with the experimental value. Abstract :